Improving Students’ English Vocabulary Mastery Through Picture Series in Class 7F MTsN 1 Probolinggo - Hasanah, Roviatul; Hikmah, Durratul (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Vocabulary mastery plays a crucial role in English language learning because it enables learners to understand meaning and communicate ideas effectively. However, many junior secondary school students experience difficulties in comprehending, remembering, and using English vocabulary in appropriate contexts. This study aimed to investigate the use of picture series as a visual learning medium to support students’ vocabulary mastery in English classrooms. The research was conducted in a junior secondary school and involved seventh-grade students. Classroom Action Research was applied through two instructional cycles consisting of planning, action, observation, and reflection stages. Data were collected using vocabulary tests and classroom observations to examine both learning outcomes and students’ learning behavior. The findings revealed noticeable improvements in students’ vocabulary mastery after the implementation of picture series. Students demonstrated higher levels of engagement, participation, and confidence during learning activities supported by sequential visual images. The use of picture series helped students understand word meanings through contextual clues, reduced learning difficulty, and supported better retention of new vocabulary. In addition, students were more active in using vocabulary in simple sentences and classroom interactions. Overall, the study indicates that picture series provide meaningful visual support that enhances vocabulary learning and creates a more interactive and motivating learning environment in junior secondary English classrooms.